Fragmentation in East Central Europe : Poland and the Baltics, 1915-1929 - Richter, Klaus (2020)
"The First World War led to a radical reshaping of Europe's political borders like hardly any previous event. Nowhere was this transformation more profound than in East Central Europe, where the collapse of imperial rule led to the emergence of a series of new states. New borders intersected centuries-old networks of commercial, cultural, and social exchange. The new states had to face the challenges posed by territorial fragmentation and at the same time establish durable state structures within an international order that viewed them at best as weak and at worst as provisional entities that would sooner or later be reintegrated into their larger neighbours' territory. An International History of Fragmentation challenges the traditional view that the emergence of these states was the product of a radical rupture that naturally led from defunct empires to nation states. Using the example of Poland and the Baltic States, it retraces the roots of the interwar states of East Central Europe, of their policies, economic developments, and of their conflicts back to deep in the First World War. At the same time, it shows that these states learned to harness the dynamics caused by territorial fragmentation, thus forever changing our understanding of what modern states can do"–